PENERAPAN ETIKA AMANAH DALAM MANAJEMEN KEPEMIMPINAN MODERN PERSPEKTIF Q.S AL-AHZAB : 72 BERDASARKAN TAFSIR AL-MISBAH - Kahfi, Al; Mahmud, Hamidullah (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
This study aims to examine the application of the ethics of trust in modern leadership through the perspective of Surah Al-Ahzab verse 72 based on the Tafsir Al-Misbah by Quraish Shihab. The ethics of trust, which includes responsibility, trust, integrity, and consistency, is crucial in facing the demands of the modern era for transparency and accountability. The Tafsir Al-Misbah emphasizes that trust is a great responsibility that is even rejected by the heavens, earth, and mountains, but is accepted by humans as a moral and spiritual trust, especially in leadership. Previous studies have shown that the ethics of trust can improve the quality of decisions and trust in the context of business and education, but there is not much understanding of this concept with a deep interpretation of the Qur'an. The results of this study are expected to enrich the literature on Islamic leadership and provide ethical guidance for modern leaders to carry out trust responsibly, strengthen credibility, and meet public expectations. Keywords: Leadership, Qs Al Ahzab: 72, Tafsir Al Misbah